Self-organization in optical systems and applications in information technology - Voron︠t︡sov, M. A. (Mikhail Alekseevich); Miller, Walter B. (Walter Blaine) (Springer series in synergetics, 1995)
Contrary to monographs on non-linear optics this book concentrates on problems of self-organization in various important contexts. The reader learns how patterns in non-linear optical systems are created and what theoretical methods can be applied to describe them. Next, various aspects of pattern formation such as associative memory, information processing, spatio-temporal instability, photo refraction, and so on are treated.